The synergy of the religious role in supporting the accelerated reduction of stunting in Kutaraja District, Banda Aceh - M. Rizal; Diza Fathamira Hamzah (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Stunting is a condition of chronic malnutrition caused by a lack of nutritional intake in the long term, resulting in a decline in the optimal growth and development of a child. In general, the incidence of stunting starts from inadequate nutritional intake during pregnancy until two years of age or more, commonly referred to as the golden period. Therefore, support from community leaders is needed to accelerate the reduction of stunting, a religious role model for the community.Objective: This study aimed to analyze the synergy of the role of religion in accelerating stunting reduction in Kutaraja District, Banda Aceh City.Methods: This was a qualitative study with a descriptive design. The informants in this study were religious and active in the Kutaraja sub-district of Banda Aceh City, with a total of 10 religions, and were selected based on specific criteria. Data were collected for two months through an in-depth interview method using a document study and questionnaires designed by the authors. Instrument validity was tested using the triangulation technique. Thematic data analysis was performed.Result: Religiosity has promoted studies related to parenting, a balanced diet, and a healthy lifestyle by directly becoming speakers in integrated service post activities, being involved in community empowerment activities called village nutrition houses, and being active as marriage counsellors in the office of religious affairs for the bride and groom.Conclusion: The synergy of religion in community activities can support the accelerated reduction of stunting, which the improvement of community participation in nutritional community empowerment activities can see.